IMPLEMENTASI USAHA SOSIAL (SOCIAL ENTERPRISE) DI SMP JUARA BANDUNG - Sobirin, Muhammad (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren Cirebon, 2021)
Free school is the hope of all parents. In fact free school is not really free. Teachers are still paid, uniforms and books are still purchased, activities still require funds, and even building rentals are not free. At the beginning of its establishment, SMP Juara Bandung made its education services free for all its students, because it received financial support from its main donor, namely the National Amil Zakat Institution (Laznas) Rumah Zakat. Because the implementation of 19 sekolah juara throughout Indonesia is a permanent burden for Rumah Zakat and this is operationally challenging, the transformation of sekolah juara is needed to realize sustainable education for SMP Juara Bandung. The transformation takes a social enterprise approach which generally consists of three qualifications, namely embedded, integrated, and external. SMP Juara Bandung applies the first qualification in the implementation of its social enterprise, namely the social enterprise qualification embedded in the form of cross-subsidies between paid general students and free scholarship students from the poor. This study aims to dig deeper into the key to the successful implementation of social enterprises at SMP Juara Bandung, the obstacles faced, the challenges after implementation, and the steps to duplicate the success of the implementation. This research is a descriptive type using a case study approach, so that a lot of information and data are obtained to answer the research objectives above. The results of the study stated that the implementation of social enterprises at SMP Juara Bandung was successful and could be duplicated in similar schools that would carry out the transformation to maintain sustainable education in their schools.